The Quest for Arabic Autobiography. (October 2015) - Lunde, Paul
The rich biographical literature of the Arabic-speaking world has been appreciated by European scholars since the inception of academic Arabic studies in the late seventeenth century and is one of the most important sources for Arabic cultural and historical studies. Less attention has been paid to Arabic self-narratives, various types of which have existed almost from the beginnings of Arabic literature in the late eighth and early ninth centuries; the majority was produced, as one might expect, by the learned elite. Dwight Reynolds has recently shown that by the thirteenth and fourteenth centuries, the scholarly autobiography had become a recognised genre, with particular features, which included childhood studies (or lack of them), higher studies under named teachers, academic controversies, positions held publications and self-justifications. These accounts seem to have almost always been attached to the beginning or end of some major work or sometimes appear as digressions within the main text. We also possess two free-standing memoirs by feudal lords, composed in the eleventh and twelfth centuries. They are filled with personal, even intimate recollections, and they both occasionally employ an informal variety of written Arabic for greater verisimilitude. This use of 'Middle Arabic' and the possible reasons for it are discussed, as is the sudden proliferation of autobiographical accounts written by Arabic speakers in European languages in the first half of the nineteenth century.